2018
DOI: 10.21833/ijaas.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wear behavior of ABS and ABS composite parts fabricated via fused deposition modelling

Abstract: Since, the material wear is an important phenomenon influencing the functionality of a part, this research was carried with the aims to study the friction and wear behaviour of parts made of ABS composite material by FDM. This study also compare the friction and wear behaviour of ABS composite with the existing acrylonitrile butadiene styrene (ABS) filament of the FDM machine. The experiment was carried out on the pin-on-disk apparatus according to ASTM G99-04 standard under dry sliding condition that were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, the higher load carrying capacity of the composites is attributed to the presence of Copper particles as discussed earlier. The observations are in line with fellow researchers [17,18]. The increased rubbing action between particles increases the coefficient of friction with increase in sliding velocity.…”
Section: Wearsupporting
confidence: 92%
“…However, the higher load carrying capacity of the composites is attributed to the presence of Copper particles as discussed earlier. The observations are in line with fellow researchers [17,18]. The increased rubbing action between particles increases the coefficient of friction with increase in sliding velocity.…”
Section: Wearsupporting
confidence: 92%
“…[5][6][7] The effect of sliding speed and contact load on wear behavior of ABS and ABS composite parts fabricated via FDM was also investigated. 8 It was shown that carbon reinforced ABS specimen had a better wear characteristics and lower frictional resistance compared to ABS specimens. However, increase on applied load and run time increased the frictional force on both samples.…”
Section: Introductionmentioning
confidence: 98%
“…The same research group also simulated the wear mechanism to figure out the probable influences of copper coating layers [17]. Sudin et al [18] compared the wear performance of ABS and ABS composites and found out that carbon fiber reinforced ABS showed less wear rate because of the high load-bearing capacity of carbon fibers. Matseevich et al [19] recommended a blend of ABS and polyvinyl chloride (PVC) for applications of floor coverings as a result of their wear analyses.…”
Section: Introductionmentioning
confidence: 99%